Managing climate risks through small ruminants in Kenyan climate-smart villages - Recha, John W.M.; Radeny, Maren A.O. (2017)
Small ruminants (goats and sheep) play an important role in rural livelihoods. About one third of the total red meat consumed in Kenya comes from small ruminants (GoK, 2015a). Small ruminants are easier to de-stock and re-stock due to their small body size, higher birth rate, and shorter generation intervals compared to large stock. Kenya Vision 2030 is the country’s development programme from 2008 to 2030, and has agriculture as a key economic pillar. Within agriculture, small ruminants have been identified as a priority sector in contributing to food security in a changing and variable climate.